Multimodel Predictive Control Approach for UAV Formation Flight. (5th May 2014) - Ru, Chang-jian; Wei, Rui-xuan; Wang, Ying-ying; Che, Jun
Abstract : Formation flight problem is the most important and interesting problem of multiple UAVs (unmanned aerial vehicles) cooperative control. In this paper, a novel approach for UAV formation flight based on multimodel predictive control is designed. Firstly, the state equation of relative motion is obtained and then discretized. By the geometrical method, the characteristic points of state are determined. Afterwards, based on the linearization technique, the standard linear discrete model is obtained at each characteristic state point. Then, weighted model set is proposed using the idea of T-S (Takagi-Sugeno) fuzzy control and the predictive control is carried out based on the multimodel method. Finally, to verify the performance of the proposed method, two different simulation scenarios are performed.